Use and limits in project finance of the capital asset pricing model: overview of highway projects - Sarmento, Joaquim Miranda; Oliveira, Miguel (European Journal of Transport and Infrastructure Research, 2018)
The Capital Asset Pricing Model (CAPM) has become the standard and most popular tool in corporate finance for assessing t he risk and return in a shareholder´s equity. It is widely used in project finance, particularly in transportation projects. Yet in highly leveraged projects, the CAPM can produce misleading results. In this paper, we show that the values that the CAPM provides for projects that use debt to finance more than 80% of their total investment are unrealistic. This finding is mainly the result of a high leverage value in the CAPM formula. We examine 20 highway projects in Portugal launched between 1999 and 2010. We argue that in transport projects with high debt levels, investors must rely on the weighted average cost of capital. We find that larger and more complex projects tend to have higher equity and capital costs. Further, the financial crisis has a significant effect on increasing the cost of these projects.